top button
Flag Notify
    Connect to us
      Site Registration

Site Registration

if (3, 4, 11) (8, 12, 63) (9, 6,64) then (12, 10, ?)

0 votes
30,038 views
if (3, 4, 11) (8, 12, 63) (9, 6,64) then (12, 10, ?)
posted Jun 12, 2018 by anonymous

Share this puzzle
Facebook Share Button Twitter Share Button LinkedIn Share Button

3 Answers

0 votes

Lets assume it is the function in the form: f (x,y)= ax + by +c, a line in three dimensions.
Considering given information, we have:
f(3,4)=11 --> 3a +4b +c = 11
f(8,12)=63 --> 8a +12b +c = 63
f(9,6)=64 --> 9a+ 6b +c = 64
f(12,10)=?
Solving first 3 equations we find a= 18; b= - 55/2 ; c= 67 => f(x,y) = 18x - (55/2) y +67, then f(10, 12)= 180 - 330 +67 = - 83

answer Sep 22, 2018 by Hanifa Mammadov
0 votes

(12-8)-(6-3)=1
(4-3)-(1-1)=1
(9-6)-(6-4)=1
(12-10)-(4-3)=1
enter image description here

answer Dec 1, 2018 by anonymous
Why ans
|12-8|-(6-3)=|4|-3=1
|3-4|-(1-1)=|-1|-0=1
|9-6|-(6-4)=|3|-2=1
 So. |10-12|-(X-Y)=|-2|-(X-Y)=1
   or. X-Y=2-1=1
Therefore answer is b which is 43
=
(12-8)-(6-3)= 4-3=1
(3-4)-(1-1)= 1-0 =1
(9-6)-(6-4)= 3-2 =1
(10-12)-(A-B)= -2-(A-B)=1

We can take 47
A=4
B=7
(10-12)-(4-7)=(-2)-(-3) = -2+3 = 1


Therefore
(10-12)-(4-7)=1



Hence proved
Second line me (3-4)-(1-1)= -1-0=-1 hoga

Logic tmhra glt hai answer 43 hi hogq
Yes answer is 1
0 votes

Easy way
(4 , 3 ,11 )
4-3 =1
[11] =1-1=0
1-0 ={ 1}☑️

( 8 , 12 , 63 )
12-8 =4
[63] =6-3=3
4 - 3 ={1}☑️

( 9 ,6 , 64 )
9-6 =3
[64] =6-4=2
3-2={1}☑️

Choose the option which is suitable on this condition
( 12 , 10 , ?)
We assume

answer Jun 18, 2020 by Shaily Singh
43 is right ans ☑️
(12,10,?)
12-10=2
[43] =4-3=1
2-1={1}☑️
...